The Influence of Printing Materials on Shrinkage Characterization in Metal 3D Printing using Material Extrusion Technology - Tran, Thi Van Nga; Long, Dang Cao; Van, Cuong Nguyen (Engineering, Technology & Applied Science Research, 2024)
This study investigates the shrinkage characteristics of various materials in metal 3D printing using Material Extrusion (ME) technology. The materials examined include 17-4PH Stainless Steel V1 and V2, Inconel 625, H13 Tool Steel V1, and A2 Tool Steel. Experiments reveal that shrinkage rates vary significantly among these materials, with 17-4PH Stainless Steel V1 exhibiting the lowest average shrinkage rate of 16.2%, while Inconel 625 shows the highest average shrinkage rate of 24.5%. These findings are critical for improving dimensional accuracy in metal 3D printing. Additionally, results demonstrate that print orientation affects shrinkage. The analysis of product accuracy reveals inconsistencies between printed dimensions and design specifications, likely influenced by printing parameters. The conclusion underscores the importance of selecting appropriate printing materials and optimizing parameters to ensure dimensional accuracy in 3D printed products.